Global economic prospects : (World Bank, 2009)
The release of this year Global Economic Prospects finds the world economy at a crossroads. Markets all over the world are engulfed in a global economic crisis, with stock markets sharply down and volatile, almost all currencies having depreciated substantially against the dollar, and risk premiums on a wide range of debt having increased by 600 or more basis points. Commodity markets too have turned a corner. Following several years of increase, prices have plummeted, and although well above their 1990s levels, they have given up most of the increases of the past 24 months. This year Global Economic Prospects analyzes the implications of the crisis for low- and middle-income countries, including an in-depth look at long-term prospects for global commodity markets and the policies of both commodity producing and consuming nations. The government responses to the recent price boom are also analyzed in this year edition. Producing-country governments have been more prudent than during earlier booms, and because they have saved more of their windfall revenues, they are less likely to be forced to cut into spending now that prices have declined. The spike in food prices tipped more people into poverty, which led governments to expand social assistance programs. Ensuring such programs are better targeted toward the needs of the very poor in the future will help improve the capacity of governments to respond effectively the next time there is a crisis.